Ecological Democracy Caring for the Earth in the Anthropocene - Lysaker, Odin (Routledge Explorations in Environmental Studies, 2024)
Ecological Democracy offers an original, thought-provoking, and engaging treatment of why and how democracy should be re-imagined in reaction to today's ecological crisis. The book explains that one need to re-imagine both the view on nature and democratic ideals within the same framework in the Anthropocene, the present geological epoch of human-made instability in the Earth system and its planetary boundaries. This book proposes unique and challenging readings of green political theory and its development of ecological democracy in the last four decades. The book is the first to offer a systematic and detailed interpretation of the role of critical theory vis-à-vis green political theory through an update regarding current non-anthropocentric critical theorists and how they may contribute to the further development of ecological democracy. Ecological Democracy builds further on deep ecology, ecophenomenology, and animism by articulating an ecocentric view on nature which defends an intrinsic moral value of all existence as well as formulating the democratic principle of all ecologically affected parties. This book provides a sophisticated, convincing, and accessible argument for how to re-imagine ecological democracy as ecocentrism in practice: ecological love. To love ecologically means caring for and encountering all existence on the Earth and in the cosmos. This book is multi-disciplinary and will be of great value to researchers as well as undergraduate and postgraduate students from many disciplines.